Influence of Ceramic Particles Size and Ratio on Surface—Volume Features of the Naturally Derived HA-Reinforced Filaments for Biomedical Applications - Aura-Cătălina Mocanu; Florin Miculescu; Cătălina-Andreea Dascălu; Ștefan Ioan Voicu; Mădălina-Andreea Pandele; Robert-Cătălin Ciocoiu; Dan Batalu; Sorina Dondea; Valentina Mitran; Lucian-Toma Ciocan (Journal of Functional Biomaterials, 2022)
The intersection of the bone tissue reconstruction and additive manufacturing fields promoted the advancement to a prerequisite and new feedstock resource for high-performance bone-like-scaffolds manufacturing. In this paper, the proposed strategy was directed toward the use of bovine-bone-derived hydroxyapatite (HA) for surface properties enhancement and mechanical features reinforcement of the poly(lactic acid) matrix for composite filaments extrusion. The involvement of completely naturally derived materials in the technological process was based on factors such as sustainability, low cost, and a facile and green synthesis route. After the HA isolation and extraction from bovine bones by thermal processing, milling, and sorting, two dependent parameters—the HA particles size (<40 μm, <100 μm, and >125 μm) and ratio (0–50% with increments of 10%)—were simultaneously modulated for the first time during the incorporation into the polymeric matrix. The resulting melt mixtures were divided for cast pellets and extruded filaments development. Based on the obtained samples, the study was further designed to examine several key features by complementary surface–volume characterization techniques. Hence, the scanning electron microscopy and micro-CT results for all specimens revealed a uniform and homogenous dispersion of HA particles and an adequate adhesion at the ceramic/polymer interface, without outline pores, sustained by the shape and surface features of the synthesized ceramic particles. Moreover, an enhanced wettability (contact angle in the ~70−21° range) and gradual mechanical takeover were indicated once the HA ratio increased, independent of the particles size, which confirmed the benefits and feasibility of evenly blending the natural ceramic/polymeric components. The results correlation led to the selection of optimal technological parameters for the synthesis of adequate composite filaments destined for future additive manufacturing and biomedical applications.